Efeitos da implantação da UHE Colíder na dinâmica fluvial e na qualidade da água do curso médio do Rio Teles Pires (Mato Grosso) - Andrade, Leila Nalis Paiva da Silva (Universidade Federal de São Carlos, 2019)
This study aimed to discuss the process of land occupation and land use, as well as evaluating river dynamics and water quality in the middle course of the Teles Pires river. This study is predicated on the hypothesis that the construction and installation of a dam on the river, which is associated with deforestation, altered the fluvial dynamics of the stretch under study, as well as affecting water quality. Five sampling campaigns were carried out—2016/2, 2017/2 and 2018/2 (July/drought) 2017/1 and 2018/1 (January/rainy)—for collection of sediment, soil and water, instrumentalization, and monitoring of the river banks. We conducted analyses of the granulometric composition of soil and sediments, using the sieving, evaporation and pipette method. We also used Kruskal-Wallis and principal component analysis (PCA) to statistically test limnological variables, hydrodynamics and bank erosion. In laboratory, we calculated water flow, the water quality index (WQI), soil loss, and the magnitude of erosion. Maps (location, land cover and land use) and sketches (cross-section, longitudinal, and erosion of the banks) were created. The results of the first chapter covered the environmental characterization and morphometry of the watershed and river stretch under study. The Teles Pires river was classified as an 8th-order channel, meandering and with rectilinear stretches. The second chapter presented the processes of land occupation and land use in the last 30 years, such as urbanization, agricultural activities and the installation of the Colíder Hydroelectric Power Plant (HPP), in the municipalities of Itaúba, Colíder and Nova Canaã do Norte. In the next chapter, we quantified the hydrodynamic variables and bank erosion before and after the installation of the power plant. The results indicate that there were significant alterations in the river channel, which changed from a lotic to a lentic environment. The banks eroded slowly, becoming subject to the process of corrosion. However, we found that erosion increased by 12% in 2018 compared to 2017. In the fourth chapter, we quantified the input of sediment transport in the Teles Pires river. Sand, silt, clay, and larger grains such as blocks, pebbles and granules were observed on the bottom of the channel. In this chapter, we also addressed the forms of hydrotransported sediment deposits in the river channel, such as islands and bars. The final chapter presents the results of limnological variables and the water quality. Studies have shown that weighting indicates optimal values in 2018/2, compared to the beginning of monitoring, the WQI value is decreasing. We can confirm that several Permanent Preservation Areas have been deforested for the installation and operation of the Colíder HPP. These hydropower projects bring benefits with the generation of electricity, but they cause harm over time, and at a certain point the damage to the environment will be irreversible. Therefore, studies that monitor the hydrosedimentology and water quality of river networks are extremely relevant, especially when changes become harmful to biota.
Effects of the installation of colider hpp on river dynamics and water quality of the middle course of Teles Pires river (Mato Grosso)
Keywords: Caracterização ambiental; Feições morfológicas; UHE Colíder; Processo de ocupação; Erosão marginal; Transporte de sedimentos; Variáveis limnológicas; Environmental characterization; Morphological features; Colíder HPP; Occupation process; Bank erosion; Sediment transport; Limnological variables; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA DE ECOSSISTEMAS; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS::GEOGRAFIA FISICA::GEOMORFOLOGIA; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS::GEOGRAFIA FISICA::HIDROGEOGRAFIA; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS::GEOLOGIA::HIDROGEOLOGIA; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS::GEOLOGIA::SEDIMENTOLOGIA; ENGENHARIAS::ENGENHARIA SANITARIA::RECURSOS HIDRICOS::PLANEJAMENTO INTEGRADO DOS RECURSOS HIDRICOS; ENGENHARIAS::ENGENHARIA SANITARIA::RECURSOS HIDRICOS::SEDIMENTOLOGIA